Penggunaan Sertifikat Vaksin Covid-19 Dalam Pencatatan Administrasi Kependudukan Ditinjau Melalui Equality Before The Law - Adi Darma, Wishwanata; Gautama, Gede Erlangga (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
The discourse on the mandatory requirements for a Covid-19 vaccine certificate in the management of population administration has become a polemic in the community. The purpose of this research is to find out about the policy regarding the mandatory requirements for the Covid-19 vaccine certificate, which is reviewed through the principle of equality before the law. This research method uses normative legal research. The results of the research study in the discussion are that the regulation of vaccination implementation is regulated in the President of the Republic of Indonesia Number 99 of 2020 concerning Vaccine Procurement and Vaccination Implementation in the Context of Combating the Corona Virus Disease 2019 (COVID-19) Pandemic as amended by Presidential Regulation of the Republic of Indonesia Number 14 of 2021 concerning Changes on Presidential Regulation of the Republic of Indonesia Number 99 of 2020 concerning Vaccine Procurement and Vaccination Implementation in the Context of Combating the Corona Virus Disease 2019 (COVID-19) Pandemic. The discourse on the mandatory use of the Covid-19 vaccine certificate in the administration of population administration and the presidential regulation sanctioning the termination of government administration services cannot be enforced because the policy is a discriminatory measure that will later be able to distinguish between those who have been vaccinated and those who have not been vaccinated and is not in accordance with the principle of Equality before. the law contained in the Indonesian constitution, namely the 1945 Constitution. Wacana syarat wajib sertifikat vaksin covid-19 dalam pengurusan administrasi kependudukan menjadi polemik dalam masyarakat. Tujuan penlitian ini untuk mengetahui wacana kebijakan syarat wajib sertifikat vaksin covid-19 di tinjau melalui asas equality before the law. Metode penelitian ini menggunakan penelitian hukum normatif. Hasil kajian penelitian dalam pembahasannya ialah Pengaturan pelaksaan vaksinasi diatur dalam Presiden Republik Indonesia Nomor 99 Tahun 2020 tentang Pengadaan Vaksin dan Pelaksanaan Vaksinasi Dalam Rangka Penanggulangan Pandemi Corona Virus Disease2019 (COVID-19) sebagaimana telah diubah dengan Peraturan Presiden Republik Indonesia Nomor 14 Tahun 2021 tentang Perubahan atas Peraturan Presiden Republik Indonesia Nomor 99 Tahun 2020 tentang Pengadaan Vaksin dan Pelaksanaan Vaksinasi Dalam Rangka Penanggulangan Pandemi Corona Virus Disease 2019 (COVID-19). Wacana syarat wajib penggunaan sertifikat vaksin covid-19 dalam pengurusan administrasi kependudukan dan sanksi perpres tentang penghentian layanan adminsitrasi pemerintahan tidak dapat diberlakukan karena kebijakan tersebut merupakan tindakan diskrimintaif yang nantinya dapat membedakan golongan yang sudah divaksin dan yang belum divaksin serta tidak sesuai dengan asas equality before the law yang terdapat dalam kosntitusi Indonesia yaitu UUD 1945.